2018
DOI: 10.1016/j.conbuildmat.2018.03.092
|View full text |Cite
|
Sign up to set email alerts
|

Durability and degradation mechanisms of GFRP reinforcement subjected to severe environments and sustained stress

Abstract: Despite the large amount of research that has been carried out to date on the use of glass fibre reinforced polymer (GFRP) bars in concrete, one factor still hindering their widespread use in civil engineering applications is the lack of comprehensive data on their long-term in-service performance. This paper presents the test results of an experimental study investigating the physical and mechanical properties of GFRP bars exposed to severe environments and subjected to different levels of sustained load. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 18 publications
2
30
0
2
Order By: Relevance
“…Since the alkaline solution contains more hydroxide ions, this effect is considered more serious. In addition, between the resin matrix and the fiber, there is a thin layer of coupling agent, which is composed of salt-based materials that are impressionable to water and alkaline environments (Fergani et al 2018). Therefore, water and alkaline solution can dissolve the coupling agent and cause local adhesion loss such as interface cracks and peeling.…”
Section: Bond Strengthmentioning
confidence: 99%
“…Since the alkaline solution contains more hydroxide ions, this effect is considered more serious. In addition, between the resin matrix and the fiber, there is a thin layer of coupling agent, which is composed of salt-based materials that are impressionable to water and alkaline environments (Fergani et al 2018). Therefore, water and alkaline solution can dissolve the coupling agent and cause local adhesion loss such as interface cracks and peeling.…”
Section: Bond Strengthmentioning
confidence: 99%
“…By comparison with the results given in some literatures [13][14][15], it could be indicated that the impact of resin matrix on the deterioration of GFRP bars would be changed as pH value and temperature increase. Under the room temperature, GFRP bars with E-CR glass fibers [9] showed higher resistance to strength degradation than the ones with Eglass fibers [7,8] exposed to the same solution conditions with the same exposure period, however, this phenomenon would exist until the environmental temperature reached up to 60 ∘ C.…”
Section: Introductionmentioning
confidence: 93%
“…It has been proved in existing studies that the direct immersion of GFRP bars in conditioned solutions is believed to be more aggressive than any practical civil engineering application [9]. However, it is an effective way to obtain the valuable results within a relatively short period of testing time and some solution conditions have been included and recommended in some test guidelines [18,19].…”
Section: Natural Aggressive Environmental Conditionsmentioning
confidence: 99%
See 2 more Smart Citations